2018
DOI: 10.1111/tbed.12857
|View full text |Cite
|
Sign up to set email alerts
|

Management of hunting waste as control measure for tuberculosis in wild ungulates in south-central Spain

Abstract: In recent decades, habitat change and the intensive management of wild ungulates for hunting have led to an increase in their populations in south-central Spain. This implies a higher generation of hunting waste, which can favour the transmission of infectious diseases, including tuberculosis (TB). The aim of this study was to assess the usefulness of the proper disposal of hunting waste as TB control measure in wild boar (Sus scrofa) and red deer (Cervus elaphus) during the 2008/2009 to 2016/2017 hunting seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The overall MTC seroprevalence found in wild ruminants (14.3%) in DNP falls within the values observed in the same species (4.3%-14.9%) in central-southern Spain (Cano-Terriza et al, 2018;García-Bocanegra et al, 2012). The significantly higher prevalence of anti-MTC antibodies detected in male and adult wild ruminants was also in agreement with those reports from Mediterranean ecosystems (Cano-Terriza et al, 2018;García-Bocanegra et al, 2012).…”
Section: A High and Widespread Circulation Of Pestiviruses Brsv Andsupporting
confidence: 90%
“…The overall MTC seroprevalence found in wild ruminants (14.3%) in DNP falls within the values observed in the same species (4.3%-14.9%) in central-southern Spain (Cano-Terriza et al, 2018;García-Bocanegra et al, 2012). The significantly higher prevalence of anti-MTC antibodies detected in male and adult wild ruminants was also in agreement with those reports from Mediterranean ecosystems (Cano-Terriza et al, 2018;García-Bocanegra et al, 2012).…”
Section: A High and Widespread Circulation Of Pestiviruses Brsv Andsupporting
confidence: 90%
“…Therefore, it is possible that some non‐significant effects were due to the sample size not being large enough if differences were smaller or rates of exposure were lower. For example, the presence of hunting waste was described in only seven farms, and it was not identified as a risk factor, whereas other authors found that eliminating this waste from the farms reduced the risk of bTB infection from wildlife 50 . The results of this study could have some underlying misclassification bias due to the lack of diagnostic sensitivity of the SITT in the field.…”
Section: Discussionmentioning
confidence: 54%
“…For example, the presence of hunting waste was described in only seven farms, and it was not identified as a risk factor, whereas other authors found that eliminating this waste from the farms reduced the risk of bTB infection from wildlife. 50 The results of this study could have some underlying misclassification bias due to the lack of diagnostic sensitivity of the SITT in the field. To reduce such biases, cases were farms confirmed as infected by isolation of MTC species, and only control farms which remained SITTnegative for three consecutive annual testing (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…High rates of pathogen circulation driven by human management are often associated to overabundance of big game; and in these cases, some infected species often play a role as facultative scavenger (e. g. wild boar, Gortazar et al 2006). In addition, the way big game waste is disposed of may allow for facultative diseasesusceptible scavengers to access infected material (Moreno-Opo et al 2012;Cano-Terriza et al 2018). For instance, in Europe, as in many other parts of the world, the changes occurring across the last 40 years have had a pronounced effect on the environment, creating a dynamic situation where pathogens or new hosts emerge o re-emerge.…”
Section: Human Related Factors Resulting In Increased Risk For Diseasmentioning
confidence: 99%